Clasificación de instituciones prestadores de servicios de salud según el sistema de cuentas de la salud de la Organización para la Cooperación y el Desarrollo Económico: el caso de Colombia - Prada-Ríos, Sergio Iván (2017)
In Colombia, public health service providers (IPS) are classified according to three complexity levels: low, medium, and high. Such is not the case with private IPS. This lack hinders comparative analyzes between private providers. To meet this need, an IPS classification algorithm was developed according to the methodology of the System of Health Accounts used in the member countries of the Organization for Economic Cooperation and Development. The database of qualified services of the Special Registry of Providers for 2015 was used as a source of information. The results show that 66% of the IPS in the country work in ambulatory care, 17% are hospitals, 11% are promotion and prevention centers, and 6% are ancillary service providers. The concentration of assets follows the opposite distribution, as it was found that hospitals have 90.5% of assets.